Is it necessary to perform a diagnostic hysteroscopy before the first embryo transfer?—A retrospective study - Fang, Jian-ye; Xu, Yang-ying; Zhang, Hui-min; Li, Duan; Yu, Ze-wei; Hao, Cui-fang (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to assess the impact of performing diagnostic hysteroscopy prior to the first in vitro fertilization (IVF) cycle on clinical pregnancy rates and live birth rates.MethodsA retrospective descriptive study was conducted from October 2019 to March 2023 at Qingdao Women and Children's Hospital, China. The study population included women under 45 years old with ultrasonographically normal uterine cavities who were undergoing their first fresh embryo transfer through in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Primary outcomes included: (1) prevalence of abnormal uterine findings detected by hysteroscopy, and (2) comparative analysis of reproductive outcomes between hysteroscopy and non-hysteroscopy groups.ResultsAmong patients undergoing hysteroscopy, 49.63% patients exhibited abnormal uterine findings, with endometrial polyps being the most common pathology (30.03%). A significantly lower rate of good-quality embryos was observed in the hysteroscopy group compared to the non-hysteroscopy group (50.38% vs. 75.11%, p < 0.05). After adjusting for embryo quality, age, BMI, AMH, duration of infertility, and endometrial thickness, multivariable analysis confirmed that the hysteroscopy group had a significantly higher clinical pregnancy rate (OR: 1.51, 95% CI: 1.142–1.997, P = 0.004) compared to the non-hysteroscopy group. In the subgroup, the clinical pregnancy rate in these two groups (the endometrial polyp group 63.49%, p = 0.014; the chronic endometritis group 64.12%, p = 0.032) was significantly higher. No statistically significant difference in live birth rate was observed between the groups.ConclusionsDiagnostic hysteroscopy effectively identifies and facilitates treatment of intrauterine abnormalities in IVF/ICSI candidates to optimize endometrial receptivity. And performance of hysteroscopy prior to IVF is significantly associated with increased clinical pregnancy rates. These findings support the recommendation for pre-transfer hysteroscopic evaluation in the first embryo transfer cycles.